Innovative principle of transformation of investment and construction entities through modern methods of reengineering - SIBIKOVSKYI, Oleksandr; SOKUROV, Artem; KOVALENKO, Vitalii; SOBOL, Denys (Ways to Improve Construction Efficiency, 2025)
The modern construction and investment sphere is undergoing significant changes under the influence of globalization processes, digital technologies and growing requirements for management efficiency. In this regard, the need to implement innovative approaches to the management of investment and construction entities is becoming more urgent. One of the most effective methods of modernization of management and operational processes is reengineering, which involves a radical rethinking of business processes in order to increase the efficiency, productivity and quality of construction projects. Reengineering in the construction sector allows you to optimize costs, increase the level of automation and implement digital management tools. Modern technologies, in particular Building Information Modeling (BIM), artificial intelligence (AI), the Internet of Things (IoT) and big data, play an important role in this, which provide highly accurate risk forecasting, optimize resource planning and improve the quality of work performance control. The use of reengineering in the construction sector contributes not only to increasing the efficiency of individual enterprises, but also to the overall improvement of interaction between all participants in the investment process. Process optimization allows you to reduce project implementation time, increase the level of communication between developers, contractors, suppliers and government agencies, which helps to increase transparency and reduce the risks of non-fulfillment of obligations. An important aspect of an innovative approach to transformations in the construction sector is strategic change management. Reengineering allows you to integrate the concept of sustainable development, which ensures a harmonious combination of economic, social and environmental goals. The use of digital technologies contributes to the transition to "smart construction", which ensures not only the quality and efficiency of processes, but also environmental sustainability, compliance with modern regulatory requirements and international standards. Thus, the introduction of reengineering in the construction industry opens up new opportunities for the development of the investment sector and increasing the efficiency of project management. The integration of digital technologies, optimization of business processes and strategic planning allow construction companies to adapt to modern challenges, increase competitiveness and ensure long-term sustainability in the market.